Effects of confining layer and ablating layer on laser-induced shock wave characteristics during laser shock processing by PVDF gauge. Issue 1 (July 2021) - Nie, X F; Tang, Y Y; Li, Y; Yan, L; Wu, H N
Abstract: The PVDF sensor is used to obtain the time variation curves of the shock wave pressure in the four states of the laser shock peening with or without confining layer and with or without ablating layer, the effects of confining layer and ablating layer on shock wave characteristics are analyzed. The results show that the confining layer limits the plasma expansion area, and the inverse bremsstrahlung absorption effect is enhanced, so that the peak pressure and pulse width of the shock wave are increased to 10 times and 2 times that under the condition of the without confining layer; The ablating layer significantly increases the peak pressure of the shock wave by improving the laser energy coupling efficiency. However, the influence of the ablating layer on the peak pressure tends to saturate with the increase of power density, the difference of the peak pressure is only 8.5% when the laser power density is 4.53GW/cm 2 . In addition, the ablating layer complicates the shock wave propagation process, and the shock wave curve presents a multi-peak structure.